HUBUNGAN PENGETAHUAN DAN PERSONAL HYGIENE DENGAN RISIKO KEJADIAN SCABIES - Ida Suryati; Def Primal; Puput Avita Sari (Universitas Pahlawan, 2022)
In Indonesia , there is a high prevalence of skin disease caused by viruses, bacteria, fungi, germs and parasites, One of the skin diseases caused by parasites is scabies. Accouirding to survey results , adullts have a 25%, prevalence of scabies , while children have about 25% ,while the highest incidence occurs in school-aged children of 30-65%. This disease is often found in densely populated areas such as orphanages. The purpose of this study was to determine the relationship between Knowledge Level and Personal Hygiene with the Risk of Scabies Incidence at the Nagari Koto Tangah Orphanage, Agam Regency. The research design uses a descriptive correlation, with a cross sectional research type. The number of samples in this study amounted to 34 respondents using a total sampling technique consisting of 2 orphanages in Nagari Koto Tangah, Agam Regency. The variables in this study were knowledge and personal hygiene with the incidence of scabies. Primary data obtained through research instruments using questionnaires. Data analysis with the chi-square statistical test (alpha < 0.05). In this study, the results obtained were that almost half of the 15 people (44.1%) foster children had poor knowledge about scabies, as many as 17 people (50%) foster children had less personal hygiene, 17 people (50%) had a risk of scabies and there is a relationship between the level of knowledge and personal hygiene with the risk of scabies with a p-value of 0.000. From the research above, the less knowledge and personal hygiene possessed by foster children, the higher the risk of scabies occurring.